LOLA, UNGGULAN SASI DI MALUKU - Hanum I. Marasabessy; Albert Ch. Nanlohy; Donald Noija; Selfie Sangadji; Grace Hutubessy (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2024)
Sasi is customary regulation which is applied to protect natural resources in land and ocean. Commercial topshell, Rochia nilotica, is a gastropod and is one of protected marine resources by sasi. There were numerous studies about sasi but the choice of R. nilotica as sasi priority in Maluku has not been concerned yet. The aim of this study is to answer the question: “Why do R. nilotica become the sasi priority in Maluku?” This study was obtained from literature reviews regarding sasi after attending the ceremonial of “buka Sasi” in Rutong village, Ambon and from interviewing several respondents from the local people. Mostly the respondents answered that R. nilotica has high economic value and has to be protected from overfishing. From the literature review, life cycle of R. nilotica does not showing any specificity and its natural abundance is not alarmed. Nevertheless, because of its large in size, long lived, late maturity and easily habitat accessible, R. nilotica is vulnerable to overfishing. Four years duration of sasi is sufficient to increase R. nilotica abundance and stabilize its population.